Mental health among recent immigrants to Sweden from Eastern Europe and the former Soviet Union - Ekblad, Solvig (Int Psychiatry, 2008)
the prevalence of mental disorders among recent immigrants to Sweden from Eastern Europe and the former Soviet Union; their access to mental health and social care facilities arising from their legal status; their utilisation of health and social services.